Zawi- iBn- Ziri and his efforts to establish the Presence of the Ziri in Granada during the reign of the kings of denominations - Khaled, Belarbi (Journal of Humanities & Social Sciences, 2021)
This study aimed at exposing the role of Zawi bin Ziri and his efforts in establishing the Ziri presence in the city of Granada during the era of the kings of denominations after his arrival from Africa to the Iberian Peninsula.This was during the last days of the Umayyad Caliphate in Cordoba and it was ruled by the BanuZizi until the fall of their king at the hands of the Almoravids in 483 AH/ 1090 CE.We will also address the reasons behind their entry to Andalusia and their stability in it as they thrived at the late era of Al- Mansour. Then in the days of his sons Abd al- Malik Al- Mudhafar and Abd al- Rahman Shingoul, and their outweighed in the army and support of his state, in addition to that we will address their stance on the tribal strife and What resulted from it as the entry of Suleiman Al Mosta’in to Cordoba. This is thanks to the efforts of Zawi bin Ziri and those with them from the Berbers after their defeat of the Qurdobians in a fierce battle in Shawwal 403 AH/ 1013AD, then finally the exposure to the most important events that the Kingdom of Granada knew during the reign of Zawi bin Ziri (403 AH- 410 AH/ 1012 AD- 1019 AD). This was done by relying on the historical method that depend on analysis, deduction, criticism and comparison. The researcher concluded the followings: - Bani- Ziri during the fourth and fifth centuries AH, the tenth and eleventh centuries AD, had a major role and influence in the political life of Andalusia, and they were not isolated from the political events that took place in it in Morocco and Andalusia. -The reasons and circumstances that pushed Zawi bin Ziri and his people to emigrate to Andalusia and leave their homeland cannot be limited only to the tyranny of Badis bin Mansour al- Ziri to rule in Africa, or to the threat of Zenata, but rather is the desire of Zawi bin Ziri to establish his own political entity after That he was unable to do so in his native Africa. - Zawy bin Ziri was distinguished by his wit and his political and military genius, as he left Ilbira island that was granted to him by Suleiman Al- Musta’in after he reached the caliphate in 403 AH/ 1013AD, in exchange for his help, and he moved to Granada, which is distinguished by its impregnable location that protects him from enemies, which is the region in which he established his kingdom in 403 AH/ 1013 AD and thus this kingdom was one of the first denominations kingdoms that appeared before the abolition of the Umayyad Caliphate in 422 AH/ 1031 CE.